Formability a review of parameters and processes that control, limit or enhance the formability of sheet metal - Emmens, Wilko C. (SpringerBriefs in applied sciences and technology., 2011)
Overview of materials and treatment aspects of manufacturability of sheet metal - Written by an industrial expert turned scientist - Concentrates on the formability of sheet metal, one of the fundamental form material is used in metalworking.